2012
DOI: 10.1200/jco.2011.34.5843
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Weekly Vinblastine in Recurrent or Refractory Pediatric Low-Grade Glioma

Abstract: Weekly vinblastine seems to be a reasonable alternative to radiation for pediatric patients with LGG who have experienced treatment failure with first-line chemotherapy. The 5-year progression-free survival observed in this phase II trial is comparable to results observed with first-line chemotherapy in chemotherapy-naive patients. The role of single-agent vinblastine and other vinca alkaloid in the management of pediatric LGGs deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 29 publications
6
129
0
Order By: Relevance
“…7,[32][33][34][35][36] Indeed, many of these patients experience multiple tumor progressions, and upfront aggressive treatment options such as radiation therapy are being used to avoid potential patient demise. Despite multiple progressions, we observed >90% survival 20 to 25 years after the diagnosis in the absence of aggressive modalities such as radiotherapy and no late mortality due to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…7,[32][33][34][35][36] Indeed, many of these patients experience multiple tumor progressions, and upfront aggressive treatment options such as radiation therapy are being used to avoid potential patient demise. Despite multiple progressions, we observed >90% survival 20 to 25 years after the diagnosis in the absence of aggressive modalities such as radiotherapy and no late mortality due to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Antitumour treatment included surgery, chemotherapy, radiotherapy and a combination of these, according to national or international protocols [25,26,27,28] (table 2). Surgery consisted of complete or partial tumour resection.…”
Section: Methodsmentioning
confidence: 99%
“…Although vinblastine is a lipophilic agent, animal studies showed low brain penetration and a low concentration in brain tissue and cerebrospinal fluid. One explanation for the activity of vinblastine in gliomas could be in its antiangiogenic activity through endothelium-directed toxicity 6,12 , a concept that is supported by preclinical data showing antiangiogenic activity with low-dose vinblastine 14,15 .…”
Section: Discussionmentioning
confidence: 91%
“…A phase ii study of weekly vinblastine in recurrent low-grade glioma demonstrated very good results, with an excellent toxicity profile in comparison with alternative strategies 6 . It might even be speculated that low-dose vinblastine was not only acting as an antiangiogenic agent, but might also have activated dendritic cells 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation